Efficient Youtube Data Mining Through Big Data Analytics - Mrs. R Lavanya, Rohit Gite, Vaibhav Chhajer (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Investigation of coordinated data has seen enormous accomplishment previously. Be that as it may, investigation of enormous scope unstructured data as video design stays a testing district. YouTube, a Google association, has over a billion customers and makes billions of perspectives. Since YouTube data is getting made in an amazingly monster total and with a correspondingly unprecedented speed, there is a colossal solicitation to store, measure and meticulously consider this huge measure of data to make it usable. The guideline objective of this task is to show by using Hadoop thoughts, how data made from YouTube can be mined and used to make zeroed in on, persistent and instructed decisions. This venture uses SQL like requests that are later continue running on Big Data using HIVE to remove the significant yield which can be used by the organization for investigation.